PENGARUH TAX AVOIDANCE DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Siti Mutiah, 09.05.52.0032; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2013)
The research objective is to obtain evidence about the impact of tax avoidance and corporate governance (Board of Directors, independent commissioners, management and ownership) to the value of the company. Object of this study is a manufacturing company listed on the Indonesia Stock Exchange during the years 2007-2011. The sample used in this study obtained by purposive sampling technique with the following criteria: Companies listed on the Indonesia Stock Exchange during 2007 to 2011. Companies that have positive earnings for the year 2007-2011. The company revealed the Independent Commissioners 2007-2011. The company revealed the management ownership in 2007-2011.Alat statistical analysis used multiple regression, where the dependent variable is the value of the company and the independent variable is tax avoidance, the board of directors, independent commissioners, management and ownership. The results of this study indicate that the effective tax rate has a negative and significant effect on firm value, the board of directors has a positive and significant effect on firm value, independent commissioner has a positive and not significant effect on firm value, management ownership has a negative and not significant effect on firm value. Keywords: Tax Avoidance, board of directors, independent commissioners, management ownership and corporate value.